Long-term implications of sustained wind power growth in the United States: Potential benefits and secondary impacts. (1st October 2016) - Wiser, Ryan; Bolinger, Mark; Heath, Garvin; Keyser, David; Lantz, Eric; Macknick, Jordan; Mai, Trieu; Millstein, Dev
Highlights: We model a scenario of the U.S. electric sector with wind reaching 35% in 2050. Scenario yields potential greenhouse-gas benefits of 85–1230 billion. Air-pollution-related health benefits are estimated at 52–272 billion. Electric-sector water use is lower by 15% (withdrawals) and 23% (consumption). Implications for risk of energy supply, local economic development, and land use. Abstract: We model scenarios of the U.S. electric sector in which wind generation reaches 10% of end-use electricity demand in 2020, 20% in 2030, and 35% in 2050. As shown in a companion paper, achieving these penetration levels would have significant implications for the wind industry and the broader electric sector. Compared to a baseline that assumes no new wind deployment, under the primary scenario modeled, achieving these penetrations imposes an incremental cost to electricity consumers of less than 1% through 2030. These cost implications, however, should be balanced against the variety of environmental and social implications of such a scenario. Relative to a baseline that assumes no new wind deployment, our analysis shows that the high-penetration wind scenario yields potential greenhouse-gas benefits of 85–1, 230 billion in present-value terms, with a central estimate of 400 billion. Air-pollution-related health benefits are estimated at 52–272 billion, while annual electric-sector water withdrawals and consumption are lower by 15% and 23% in 2050, respectively. We also find that a high-wind-energy future would have implications for the diversity and risk of energy supply, local economic development, and land use and related local impacts on communities and ecosystems; however, these additional impacts may not greatly affect aggregate social welfare owing to their nature, in part, as resource transfers.